APLIKASI PENCARIAN ASISTEN RUMAH TANGGA “ASISTENKU” PADA MODUL MITRA BERBASIS ANDROID - Soni Satria Nugroho; Anie Rose Irawati; Ardiansyah Ardiansyah (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
The benefits of information technology are currently experiencing very rapid development. One of the rapidly developing information technology is the internet. Internet technology can access information anywhere and anytime, at a very low cost. The internet can be accessed using a smartphone and is useful for communicating or searching for information. Information is also needed in a household assistant service offering, so that a prospective assistant can more quickly find an employer without having to come to the service provider. In this study, an application was made to look for android-based household assistants. This application helps users to get information about the existence of household assistant jobs by displaying work information needed according to their fields. Applications are tested by functional and non-functional testing methods using a Likert scale. Based on functional testing it is known that the application has fulfilled the required functions and based on non-functional testing it is known that the respondents' assessment of the application is on average worth 90.5% which means it is very good.